1999
DOI: 10.1081/pdt-100101400
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2 Binding and Incorporation in PLGA Microsphere Delivery Systems

Abstract: The objective of this research was to determine the binding capacity and kinetics, and total incorporation of recombinant human bone morphogenetic protein-2 (rhBMP-2) in microspheres made from hydrophilic and hydrophobic poly(lactide-co-glycolide) (PLGA). Polymers were characterized by molecular weight, polydispersity, and acid number. Microspheres were produced via a water-in-oil-in-water double emulsion system and characterized for bulk density, size, specific surface area, and porosity. Protein concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…[1][2][3][4][5][6] Mucoadhesive polymers may fulfill the desirable features of a prolonged residence time at the site of drug absorption owing to increased contact with the absorbing mucosa, resulting in a steep concentration gradient to favor drug absorption, and localization in specified regions to improve and enhance the bioavailability of the drug. 7 Factors such as cross-linking status, ionic modification, and salt formation can significantly influence the ability of a material to show substantial mucoadhesion in an in vitro system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Mucoadhesive polymers may fulfill the desirable features of a prolonged residence time at the site of drug absorption owing to increased contact with the absorbing mucosa, resulting in a steep concentration gradient to favor drug absorption, and localization in specified regions to improve and enhance the bioavailability of the drug. 7 Factors such as cross-linking status, ionic modification, and salt formation can significantly influence the ability of a material to show substantial mucoadhesion in an in vitro system.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable microspheres have been extensively investigated as delivery systems for biologically active peptides and proteins (Schrier & DeLuca, 1999;Woo et al, 2001). Sustained-release characteristics of microspheres reduce the need for frequent administrations and enhance patient compliance by maintaining in vivo drug levels in the therapeutic range (Okada et al, 1991).…”
Section: Microspheres and Microparticles As Protein Stabilizermentioning
confidence: 99%
“…PLGA microsphere delivery systems for rhBMP-2 have been previously reported [16,[24][25][26]. In a study of various carriers for rhBMP-2 microspheres, Rodgers et al [26] found that methylcellulose elicited more fibrosis than did carboxymethylcellulose (CMC) and that CMC alone (ie, with no added rhBMP-2 microspheres) showed a mild promotion of bone growth.…”
Section: Introductionmentioning
confidence: 99%